The Lord is my shepherd : Psalm 23 for the life of the church - Briggs, Richard S., 1966- (Grand Rapids, MI. Baker Academic, 2021)
There are few biblical texts more familiar to Christians than Psalm 23: "The Lord is my shepherd; I shall not want . . ." It is one of the Bible's most popular passages, retaining a special place in ministry and giving hope to the burdened. Internationally recognized Old Testament scholar Richard Briggs helps readers understand the power and vision of Psalm 23. He offers a close word-by-word and phrase-by-phrase reading of this classic and beloved text, showing how it can speak afresh to the life of the church today. Briggs explores the reception of Psalm 23 down through the ages, covers background issues, and examines the ways the psalm addresses practical issues such as stress, death, enemies, and hope. The book helps reconnect the Christian church to the Old Testament, making it perfect for sermon preparation and small group study
Includes bibliographical references and indexes
Keywords: Bible. -- Criticism, interpretation, etc